Relationship Between Glycosylated Hemoglobin Concentration and Prognosis of Acute ST-Segment Elevation Myocardial Infarction in Non-Diabetic Patients - Liu Z; Gao J; Hu W; Yan P; Lu J; Lei T; Xia J (International Journal of General Medicine)
Zhao Liu,1,2 Jie Gao,1 Wenying Hu,3 Pengyong Yan,3 Jun Lu,1 Tao Lei,1 Juan Xia1 1Department of Endocrinology, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 3Department of Cardiology, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Juan Xia, Department of Endocrinology, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, No. 164 of Lanxi Road, Putuo District, Shanghai, People’s Republic of China, Email xiaj913@163.comObjective: To investigate the relationship between glycosylated hemoglobin (HbA1c) concentration at admission and the prognosis of acute ST-segment elevation myocardial infarction (STEMI) in non-diabetic patients.Methods: A total of 142 non-diabetic patients with acute STEMI who underwent emergency percutaneous coronary intervention (PCI) in our hospital between January 2023 and December 2024 were enrolled in this study. HbA1c levels and baseline data for all patients were obtained at admission. According to the HbA1c level, patients were divided into a normal blood glucose level group (group A, HbA1c & lt; 5.7%, N = 57) and a pre-diabetic group (group B, 5.7% ≤ HbA1c ≤ 6.4%, N = 85). The occurrence of major cardiovascular events (MACE) was compared between the two groups after PCI during one-year follow-up.Results: The levels of serum FPG, BNP and the number of patients with multivessel diseases in group B were higher than those in group A (all p < 0.05). The LVEF in group B was significantly lower than in Group A (P = 0. 017). The total incidence of major cardiovascular events (MACE) within 1 year after PCI was significantly higher in group B than in group A (P = 0. 047). In addition, the risk of MACE in group B was 4.98 times higher than that in group A.Conclusion: HbA1c can be used as an independent predictor of MACE in non-diabetic STEMI patients. The control of blood glucose levels in pre-diabetic patients with STEMI should be given high emphasis to improve prognosis after PCI.Keywords: prediabetic lesions, glycosylated hemoglobin, acute ST-segment elevation myocardial infarction, major cardiovascular events